2019
DOI: 10.1038/s41598-019-46899-x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Compactness based on CT to predict prognosis after multimodal treatment for esophageal squamous cell carcinoma

Abstract: We aimed to establish a risk model using computed tomography-based compactness to predict overall survival (OS) and progression-free survival (PFS) after multimodal treatment for esophageal squamous cell carcinoma (ESCC). We extracted pre-treatment computed tomography-based tumor data (volume, surface area, and compactness) for 512 cases of ESCC that were treated at 3 centers. A risk model based on compactness was trained using Cox regression analyses of data from 83 cases, and then the model was validated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Nevertheless for potential non-responders to CRT it would be pivotal to identify these patients prior to therapy. The prognostic model may be further improved by the implementation of CT derived parameters, as a recent multicenter study showed promising results regarding risk stratification based on CT data 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless for potential non-responders to CRT it would be pivotal to identify these patients prior to therapy. The prognostic model may be further improved by the implementation of CT derived parameters, as a recent multicenter study showed promising results regarding risk stratification based on CT data 23 .…”
Section: Discussionmentioning
confidence: 99%
“…2008–2011 CT Inst 1: 120 kVp, 406 mAs, 3–5 mm Inst 2: 120 kVp, 150 mAs, 3–8 mm Voxel size: 1 × 1 × 5 mm3 dCCRT 87 (train) 46 (val.) HF In-house (Matlab 2015b) No Wang: 2019 [ 60 ] ESCC Train 2012–2016 Val. 2004–2014 CT 120 kV, 180-280 mA, 3 mm CCRT and RT alone 83 (train) 98 + 283 (val.)…”
Section: Resultsmentioning
confidence: 99%
“…The majority of imaging modalities mentioned in the retrieved studies were PET (20/37) [ 28 , 30 , 34 40 , 44 47 , 49 , 50 , 52 , 55 , 56 , 59 , 61 ], CT (16/37) [ 29 , 31 – 33 , 41 , 43 , 48 , 51 , 53 , 54 , 57 , 58 , 60 , 62 64 ], and one cone beam CT (CBCT) [ 42 ]. Although the search criteria included MRI, we did not locate any eligible study in our search.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations